Analisis Efisiensi Saluran Distribusi Melalui Pendekatan Transportasi Pada UMKM Kerupuk Ikan Tengiri Desa Gedangan Kecamatan Kutorejo Kabupaten Mojokerto - Rozi, Fatkhur; Agatin, Reny Rizqi (IQTISHODUNA, 2019)
The rapid development of the business world today requires businesses to determine appropriate and targeted strategies, and the strategy carried out by business actors are expected to be able to face and win the competition in the business world, one of the strategy applied is the distribution channel. Therefore, distribution channel decisions often involve a long-term commitment to other agencies or companies. This study aims to determine the value of the efficiency of the distribution channel with the least cost and Vogel's methods, in addition to knowing the efficient path of the distribution channel with the shortest route model. This research includes descriptive quantitative research through a mathematical approach where the aim is to find out the value of the efficiency of the distribution channel, by taking census technical sampling of 31 businessmen in the fish crackers in the village of Gedangan. Data analysis aims to simplify data processing so that it is easy to read and interpret. Data is collected by observation, interview and documentation. The results of this study indicate that the same minimum total cost is obtained between the least cost and Vogel's method. The shortest distance route model is accomplished in all category.